2013
DOI: 10.1111/bjhp.12060
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on non‐reflective action: An exploratory think‐aloud study of self‐report habit measures

Abstract: ObjectivesWithin health psychology, habit – the tendency to enact action automatically as a learned response to contextual cues – is most commonly quantified using the ‘Self-Report Habit Index’, which assesses behavioural automaticity, or measures combining self-reported behaviour frequency and context stability. Yet, the use of self-report to capture habit has proven controversial. This study used ‘think-aloud’ methods to investigate problems experienced when completing these two measures.DesignCross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 51 publications
1
57
0
2
Order By: Relevance
“…matches that of researchers interpreting the data (Gardner & Tang, 2014). An additional problem inherent to self-report is inattentive responding, which can distort effects (Maniaci & Rogge, 2014).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…matches that of researchers interpreting the data (Gardner & Tang, 2014). An additional problem inherent to self-report is inattentive responding, which can distort effects (Maniaci & Rogge, 2014).…”
Section: Discussionsupporting
confidence: 69%
“…Future work, ideally using non‐student samples, might compare our items against less subjective habit measures, such as recall of sequential procedures (Judah, Gardner, & Aunger, ), or implicit association tests (Labrecque & Wood, ). ‘Think aloud’ methods might assess whether participants’ comprehension matches that of researchers interpreting the data (Gardner & Tang, ). An additional problem inherent to self‐report is inattentive responding, which can distort effects (Maniaci & Rogge, ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, people's recollection as to whether a behaviour was initiated or performed automatically may be inherently unreliable as a measure of habit. To further illustrate this point, Gardner and Tang (2014) recently found that participants are likely to encounter a considerable number of difficulties recalling actions, cues to action, and the extent to which they are 'automated' when completing self-reported habit indexes.…”
Section: Downloaded By [Curtin University Library] At 02:03 11 Octobementioning
confidence: 99%
“…He indicates that self-report habit indexes, in which individuals reflect on the automaticity of action through their previous experience, represent the typical means to measure habit (Gardner, Abraham, Lally, & de Bruijn, 2012;Verplanken & Orbell, 2003). Gardner touches upon some of the limitations of such measures, indicating that the measures neglect cues (Sniehotta & Presseau, 2012) and that some of the items likely invite responses consistent with frequency of action rather than automaticity (Gardner & Tang, 2014 A c c e p t e d M a n u s c r i p t RUNNING HEAD: Self-Reports of Habit 4 problematic in that individuals are unlikely to have access or awareness of the cues and associated responses that give rise to habitual action. Reliance on such indexes may lead to erroneous inferences in the extent to which behaviours are controlled by habitual processes.…”
mentioning
confidence: 99%
“…2. One SRHI item, which is excluded from the SRBAI, appears to relate to the experience of blocking the habit impulse ('Behaviour X is something that makes me feel weird if I do not do it'), though validation work has shown that participants struggle to comprehend the meaning of 'feeling weird' (Gardner et al, 2012;Gardner & Tang, 2014).…”
Section: Notesmentioning
confidence: 99%